2008
DOI: 10.1111/j.1439-0329.2008.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Nordic and Baltic populations of Chondrostereum purpureum: a potential herbicide biocontrol agent

Abstract: We analysed genetic variation in the natural populations of a potential herbicide biocontrol agent, Chondrostereum purpureum, in Nordic and Baltic countries using random amplified microsatellite markers. The results showed high genetic diversity among the populations of this fungus, but almost a complete lack of local differentiation. The results implicate that any local strain from the area can be used as a biocontrol agent without a fear of introducing new genotypes to treatment areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…These populations are characterised by having a high genetic diversity and a low geographic differentiation within continents Högberg, Stenlid, and Karlsson 1995;Högberg, Holdenrieder, and Stenlid 1999;Boisselier-Dubayle, Perreau-Bertrand, and Lambourdiere 1996;Bernier 1996, 1999;Saville, Yoell, and Anderson 1996;Vasiliauskas and Stenlid 1998;James, Porter, Hamrick, and Vilgalys 1999;Kauserud and Schumacher 2003;Vartiamäki, Uotila, Vasaitis, and Hantula 2008). In this work, results from the microsatellite and M13 loci generally gave a similar pattern for the genetic population structure of P. gigantea.…”
Section: Discussionsupporting
confidence: 72%
“…These populations are characterised by having a high genetic diversity and a low geographic differentiation within continents Högberg, Stenlid, and Karlsson 1995;Högberg, Holdenrieder, and Stenlid 1999;Boisselier-Dubayle, Perreau-Bertrand, and Lambourdiere 1996;Bernier 1996, 1999;Saville, Yoell, and Anderson 1996;Vasiliauskas and Stenlid 1998;James, Porter, Hamrick, and Vilgalys 1999;Kauserud and Schumacher 2003;Vartiamäki, Uotila, Vasaitis, and Hantula 2008). In this work, results from the microsatellite and M13 loci generally gave a similar pattern for the genetic population structure of P. gigantea.…”
Section: Discussionsupporting
confidence: 72%
“…The population analysis conducted by Vartiamäki et al (2008b) also suggested that C. purpureum has no asexual reproduction, a result in accordance with previous studies showing no support for clonal reproduction in C. purpureum , Ramsfield et al 1999. Thus, in the lack of clonal propagation the genes of the biocontrol strain will mix with those of other individuals in the same population as soon as basidiospores are produced, and the original genotype will not spread outside the treated areas.…”
Section: Biosafety Aspectssupporting
confidence: 70%
“…The populations showed only a very low degree of geographical differentiation (Vartiamäki et al, 2008b). Therefore, either a gene flow occurs naturally throughout Finland and the Baltic countries, or the fungus has such a high population size that the frequencies of selectively neutral markers studied change extremely slowly.…”
Section: Biosafety Aspectsmentioning
confidence: 99%
“…Numerous studies have shown that the use of C. purpureum is not dangerous for non-targeted hosts and the pathogenic fungus does not pose a risk of becoming epidemic (de Jong et al, 1996;Wall, 1997;Becker et al, 1999Becker et al, , 2005Gosselin et al, 1999;Vartiamä ki et al, 2008a). Published research in the field of vegetation management states that the biological agent reduces the stump sprouts of certain species, such as paper birch (Betula papyrifera Marsh.)…”
mentioning
confidence: 98%